THE PROFILE OF TEACHER’S UNDERSTANDING ON STUDENT’S MATHEMATICS ABILITY BASED ON TEACHER’S TEACHING EXPERIENCE AT SMPN 1 GANTARANGKEKE - Hari Aningrawati Bahri (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The objectives of the research were discover the profile of the teachers understanding by revealing the depth of students’ knowledge based on misconception and precondition knowledge in solving the questions.The research was descriptive with qualitative approach. The researcher was the main instrument guided by mathematics ability diagnostic test, format of teachers written analysis result, and interview guidance which were valid. The data of the research was collected through test; then, the test was analyzed by the teachers in writing and verified through interview. The subjects of the research were teachers and student, namely one student of class IXB at SMPN 1 Gantarangkeke and two teachers with qualification of one novice teacher and one senior teacher. The results of the research showed that: (1) in identifying the student’s misconception, the novice teacher’s perspective and senior teacher’s perspective were similar. They thought that procedure mistake was also the student’s misconception, the teachers did not differentiate the student’s mistake whether its procedural or misconception; (2) the understanding of novice teacher and senior teacher on the students precondition knowledge of the subject understood that the mistake done by the student did not remember precondition material in solving the problem; (3) the understanding of senior teacher on the students precondition knowledge was the subject understood that the mistake done by the student was due to the student did not remember precondition material in solving the problem; the follow up plan for novice teacher referred to instrumental or procedural understanding, the divergent learning was centered in one way, the PCK component of novice teacher did not develop equally between the students knowledge identification and follow up plan; (5) the follow up plan for senior teacher did not only notice the student’s conceptual knowledge, but also how to build the student’s skill in solving the question based on the right procedure, able to demonstrate the connection in learning between the knowledge on student and pedagogic knowledge